The Influence of Kaizen Culture and Work Rotation on the Performance of PT. Mitsuba Indonesia Tangerang - Nofrita Indah Puspita Sari; Gurnari Courtney; Pafgett Torsten; Haferlach Jaroslaw (Journal Markcount Finance, 2023)
This study evaluates the Influence of kaizen culture and job rotation on employee performance at PT Mitsuba Indonesia Tangerang. The research method used was a survey using a questionnaire as a data collection instrument. The research sample was PT Mitsuba Indonesia Tangerang employees who were randomly selected. The collected data were analyzed using regression analysis. The study results show that the kaizen culture positively and significantly affects employee performance at PT Mitsuba Indonesia Tangerang. In addition, job rotation also has a positive and significant impact on employee performance. Furthermore, the study's results also show that the kaizen culture and work rotation both positively and significantly affect employee performance at PT Mitsuba Indonesia Tangerang. Based on the results of this study, it is suggested that PT Mitsuba Indonesia Tangerang improve the application of a kaizen culture and work rotation as a strategy to improve employee performance.